Synchronisation and chaos in a laser diode driven by a resonant tunnelling diode - Romeira, B.; Figueiredo, J.; Slight, T.; Wang, L.; Wasige, E.; Ironside, Charlie; Quintana, J.; Avedillo, M. (2008)
The authors report on a hybrid integration of a resonant tunnelling diode laser diode driver configuration that can operate as a self-oscillating circuit, and when externally perturbed shows regions of frequency division and frequency multiplication, quasi-periodic and chaotic oscillations, both in the optical and electrical outputs. The authors also demonstrate that this optoelectronic circuit is well described as a Liénard's oscillator. The synchronisation capabilities of the circuit have potentially novel functions for optical communications systems including clock recovery, clock division and data encryption. © 2008 The Institution of Engineering and Technology.